Optimalisasi Penggunaan Zakat Untuk Memutus Rantai Kemiskinan di Desa Laud Dendang Kecamatan Percut Sei Tuan - Lubis, Nurul Rafiqoh; Nasution, Yenni Samri Juliati (Journal of Student Development Informatics Management (JoSDIM), 2023)
This study aims to examine the management of zakat and the empowerment of the poor in an effort to alleviate poverty in the village of Laud Dendang, Deli Serdang.Data collection methods are conducted through field studies, interviews, and data analysis.The results showed that the management of zakat by the Badan Amil Zakat Nasional (BAZNAS) has had a positive impact in empowering the poor.Zakat funds collected and managed properly are used for the program "reaching sustenance and Divine Blessing" which aims to send children who drop out of school.The Program involves local government, community leaders, educators, students, and local security.With this program, children who drop out of school can return to school and get assistance in the form of tuition payments, uniforms, and other school needs.The Program also has robust monitoring and evaluation mechanisms to ensure its effectiveness. The sustainability of the program and transparency in the management of zakat funds are also a focus in efforts to alleviate poverty.The results of this study provide insight into how zakat management can empower the poor and serve as an example for similar programs in other regions. The Program" reaching sustenance and Divine Blessing " is expected to provide long-term benefits and help alleviate poverty in Laud Dendang Village.